2004
DOI: 10.1258/135763304323070751
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of neuropsychological testing of older adults via videoconference: implications for assessing the capacity for independent living

Abstract: We examined the feasibility of administering neuropsychological tests via videoconference. Twenty-nine participants from central Alberta volunteered for the study. All were 60 years of age or older and were without neurological or psychiatric disturbance. All the participants were tested under two experimental conditions: face to face and via videoconference (at a bandwidth of 336 or 384 kbit/s). Memory and learning, letter fluency, expressive word knowledge, reasoning, verbal attention and visual-spatial proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 15 publications
1
57
1
Order By: Relevance
“…Neuropsychological tests relying upon verbal instructions and responses are particularly well suited to VTC administration, and good agreement between VTC and face-to-face testing has been seen in several studies. Montani et al (1997) were among the first to explore the use of the Mini-Mental State Examination (MMSE) and other cognitive screening tests in elderly inpatients, and this was followed by other investigations using a variety of brief measures in psychogeriatric (Ball & Puffett, 1998; Menon et al, 2001) and healthy older subjects (Hildebrand, Chow, Williams, Nelson, & Wass, 2004). Vestal, Smith-Olinde, Hicks, Hutton, and Hart (2006) demonstrated good agreement between neuropsychological measures of language administered to a small group of patients with dementia in face-to-face and VTC conditions, and promising telehealth-based neuropsychological assessment programs have been described in military settings as well (Clement, Brooks, Dean, & Galaz, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological tests relying upon verbal instructions and responses are particularly well suited to VTC administration, and good agreement between VTC and face-to-face testing has been seen in several studies. Montani et al (1997) were among the first to explore the use of the Mini-Mental State Examination (MMSE) and other cognitive screening tests in elderly inpatients, and this was followed by other investigations using a variety of brief measures in psychogeriatric (Ball & Puffett, 1998; Menon et al, 2001) and healthy older subjects (Hildebrand, Chow, Williams, Nelson, & Wass, 2004). Vestal, Smith-Olinde, Hicks, Hutton, and Hart (2006) demonstrated good agreement between neuropsychological measures of language administered to a small group of patients with dementia in face-to-face and VTC conditions, and promising telehealth-based neuropsychological assessment programs have been described in military settings as well (Clement, Brooks, Dean, & Galaz, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that teleneuropsychology shows good agreement with traditional in-person assessment (Jacobsen, Sprenger, Andersson, & Krogstad, 2003; Kirkwood, Peck, & Bennie, 2001; Hildebrand, Chow, Williams, et al, 2004; Loh, Ramesh, Maher, et al, 2004; Vestal, Smith-Olinde, Hutton, & Hart, 2006). A feasibility study of teleneuropsychology in older subjects with and without dementia found correlations between 0.5 and 0.8 on a brief battery of common neuropsychological tools administered in-person and via videoconference (Cullum, Weiner, Gehrmann, & Hynan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…(10, 11, 12) VC evaluation of language has also been performed with AD patients. (13) There is a small literature on the use of videoconferencing (VC) to diagnose and treat cognitive disorders in older adults (14, 15, 16, 17) including a publication on the diagnosis of Alzheimer disease (AD) in persons with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%